The prophylactic antibiotics in the hospital environment - Silva, Celso; Czarnevicz, Daniel; Ferreira, Ciro; Neirotti, Rubens; Blanco, Luis (Cirugía del Uruguay, 1994)
lnfectious processes continue to be, even today, the main cause of post-operative complications; with antibiotics and their prophilactic administra/ion it was thought that there would be a frank decrease of these complications but the result was not the expected one. The authors analyse the real utility of intranosocomial prophilactic antibioticotherapy by means of the study of 729 patients divided into two groups: 373 were studied retrospectively and 346 prospectively and with a protocol